The Role of Schools in Shaping Moderate Awareness for Learners - Sahri Sahri; Suudin Aziz (Fakultas Agama Islam Universitas Billfath, 2023)
This article aims to discuss the role of schools in shaping moderate awareness in young people as an effort to prevent radicalization and identity-based conflicts. This research highlights the importance of schools as educational institutions and social environments in shaping students' attitudes, values, and behaviors. This type of research is a literature study. In carrying out data collection techniques, it is carried out by reviewing literature and relevant library materials in the form of books and articles. Meanwhile, analysis of the data is done in three steps, First, the determination of the design or model; second, the disbursement of main data or primary data, namely individual texts; and third, the search for contextual knowledge so that the research carried out is not in a vacuum, but relates to other factors. The result of this research is that the school is not only a place for the transfer of academic knowledge but also an institution that plays a role in shaping the personality and character of students. Teachers and teaching staff have a central role as role models who guide students toward moderate understanding and behavior. Through daily interactions with students, schools have the opportunity to teach values such as tolerance, mutual respect, and inclusivity.